2013
DOI: 10.1002/cjoc.201300204
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Initial Decomposition Pathways of the n‐Alkane/Nitroalkane Binary Mixture

Abstract: Addition of nitroalkanes into n-alkanes can lower the activation barriers of free-radical production and accelerate the decomposition of n-alkanes at relatively low temperatures. Four initial decomposition mechanisms of the n-butane/nitroethane binary mixture were proposed for the promoting effect and considered theoretically at the B3LYP, BB1K, BMK, MPW1K, and M06-2X levels with MG3S basis set. Energetics above was compared to high-level CBS-QB3 and G4 calculations. Calculated results confirm the feasibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The improvement effect on the conversion is first increased and then decreased, and the addition of 1, 2, and 4 wt % nitropropane increased the conversion of n -decane from 9.5% to 21.6%, 24.9%, and 26.8% at 887 K. In the presence of the initiator, the C–C bond cleavage reaction is no longer the initial decomposition reaction. By contrast, the C–N bond cleavage reaction of nitropropane, which produces propyl and nitro groups, changes the initial decomposition pathways and promotes the pyrolysis of the fuel. , The promoting effect of the initiator can be reflected in the reaction rate constant, which was calculated and is shown in Figure . Compared to the n -decane pyrolysis without an initiator, nitropropane as a good performance initiator additive to fuel increases the reaction rate constant when the fuel temperature is lower than 830 K, and the reaction rate constant of initiated pyrolysis decreases gradually to the same value of the n -decane pyrolysis without an initiator.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The improvement effect on the conversion is first increased and then decreased, and the addition of 1, 2, and 4 wt % nitropropane increased the conversion of n -decane from 9.5% to 21.6%, 24.9%, and 26.8% at 887 K. In the presence of the initiator, the C–C bond cleavage reaction is no longer the initial decomposition reaction. By contrast, the C–N bond cleavage reaction of nitropropane, which produces propyl and nitro groups, changes the initial decomposition pathways and promotes the pyrolysis of the fuel. , The promoting effect of the initiator can be reflected in the reaction rate constant, which was calculated and is shown in Figure . Compared to the n -decane pyrolysis without an initiator, nitropropane as a good performance initiator additive to fuel increases the reaction rate constant when the fuel temperature is lower than 830 K, and the reaction rate constant of initiated pyrolysis decreases gradually to the same value of the n -decane pyrolysis without an initiator.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, the C−N bond cleavage reaction of nitropropane, which produces propyl and nitro groups, changes the initial decomposition pathways and promotes the pyrolysis of the fuel. 37,47 The promoting effect of the initiator can be reflected in the reaction rate constant, which was calculated and is shown in Figure 8. Compared to the n-decane pyrolysis without an initiator, nitropropane as a good performance initiator additive to fuel increases the reaction rate constant when the fuel temperature is lower than 830 K, and the reaction rate constant of initiated pyrolysis decreases gradually to the same value of the n-decane pyrolysis without an initiator.…”
Section: Effect Of Nitropropane On N-decane Conversionmentioning
confidence: 99%
“…Chakraborty et al 24 found that the added initiator had an effect when the fuel pyrolysis rate was low, and its effect was negligible when the fuel pyrolysis rate was high. Guan et al 26,27 studied the initial pyrolysis path of n-alkane/nitro-alkane-initiated pyrolysis by the quantum chemical calculation method and obtained four possible initial reactions according to the calculation results of activation energy. In summary, the previous research on initiated pyrolysis focuses on macroscopic aspects such as improving the fuel pyrolysis rate and heat sink.…”
Section: Introductionmentioning
confidence: 99%